The Impact of Mechanical Energy Assessment on Mechanical Ventilation: A Comprehensive Review and Practical Application - Burša, Filip; Oczka, David; Jor, Ondřej; Sklienka, Peter; Frelich, Michal; Stigler, Jan; Vodička, Vojtech; Ekrtová, Tereza; Penhaker, Marek; Máca, Jan (Medical science monitor, 2023)
Mechanical ventilation (MV) provides basic organ support for patients who have acute hypoxemic respiratory failure, with acute respiratory distress syndrome as the most severe form. The use of excessive ventilation forces can exacerbate the lung condition and lead to ventilator-induced lung injury (VILI); mechanical energy (ME) or power can characterize such forces applied during MV. The ME metric combines all MV parameters affecting the respiratory system (ie, lungs, chest, and airways) into a single value. Besides evaluating the overall ME, this parameter can be also related to patient-specific characteristics, such as lung compliance or patient weight, which can further improve the value of ME for characterizing the aggressiveness of lung ventilation. High ME is associated with poor outcomes and could be used as a prognostic parameter and indicator of the risk of VILI. ME is rarely determined in everyday practice because the calculations are complicated and based on multiple equations. Although low ME does not conclusively prevent the possibility of VILI (eg, due to the lung inhomogeneity and preexisting damage), individualization of MV settings considering ME appears to improve outcomes. This article aims to review the roles of bedside assessment of mechanical power, its relevance in mechanical ventilation, and its associations with treatment outcomes. In addition, we discuss methods for ME determination, aiming to propose the most suitable method for bedside application of the ME concept in everyday practice.
Keywords: Aggression; poškození plic mechanickou ventilací; Respiratory Distress Syndrome; Humans; lidé; umělé dýchání; agrese; dýchání; Ventilator-Induced Lung Injury; syndrom dechové tísně; Respiration, Artificial; Respiration; Thorax; hrudník